Modelo de mensuração de mercado para bens duráveis: o caso de condicionadores de ar para uso residencial - Flores, Dalva Regina (1997)
It discusses a model to measure durable goods market by cities. The modeling process assumes that the function must be established by analyzing the stage of the product i n the diffusion process, each city i s a unit represented by secondary data, and the secondary data are determined by knowing the characteristics of the consumer behavior o f the product In the model the residuals are presented as strategic marketing tools. I t is exposed an application to air conditioning market.